2013
DOI: 10.1016/s2095-3119(13)60342-1
|View full text |Cite
|
Sign up to set email alerts
|

Application of Mulching Materials of Rainfall Harvesting System for Improving Soil Water and Corn Growth in Northwest of China

Abstract: The ridge and furrow rainfall harvesting (RFRH) system is used for dryland crop production in northwest China. To determine the effects of RFRH using different mulching materials on corn growth and water use efficiency (WUE), a field experiment was conducted during 2008-2010 at the Heyang Dryland Experimental Station. Four treatments were used in the study. Furrows received uncovered mulching in all RFRH treatments whereas ridges were mulched with plastic film (PF), biodegradable film (BF), or liquid film (LF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Detecting soil moisture conservation benefits of mulches can be difficult given confounding influences of crop and weed growth, precipitation, and irrigation. Nonetheless, in all studies reviewed here, soil moisture beneath BDMs was equal to or greater than in PEM [31][32][33][34][35][36][37][38][39][40]).…”
Section: Soil Moisturementioning
confidence: 99%
“…Detecting soil moisture conservation benefits of mulches can be difficult given confounding influences of crop and weed growth, precipitation, and irrigation. Nonetheless, in all studies reviewed here, soil moisture beneath BDMs was equal to or greater than in PEM [31][32][33][34][35][36][37][38][39][40]).…”
Section: Soil Moisturementioning
confidence: 99%
“…Singh et al (2011) observed increased soil water content and improved crop growth and yield determining attributes of wheat under mulch and found that mulch suppressed whole of season soil evaporation by 35-40 mm. Han et al (2013) reported 8.2 and 7.3% average soil water storage at depths of 0-200 cm, 20.4 and 19.4% grain yield and 23.3 and 21.7% water use efficiency (WUE) higher with plastic film and biodegradable film than no mulch, respectively in maize crop. In another study, immediate maize post harvest tillage with mulch application (maize straw mulch @ 5 t/ha) showed about 3 times higher soil moisture conservation efficiency than control (Sharma et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies also believe that plastic film can cause white pollution, which limits the application of plastic film coverage in agriculture [26]. However, with the progress of science and technology, degradable plastic film, liquid plastic film, and other new eco-friendly plastic films are available which can be applied in production [29][30][31][32]. The application of these new types of plastic film reduces the environmental pollution caused by the degradation of plastic film cover and will play a good role in promoting the application of plastic film in agriculture.…”
Section: Discussionmentioning
confidence: 99%